TRAUMA AND VULNERABILITY IN TIM WINTON’S CLOUDSTREET - Alice R. J., Anne; E. Anita (International Journal of Research -GRANTHAALAYAH, 2026)
The paper entitled “Trauma and Vulnerability in Tim Winton’s Cloudstreet” investigates the interrelation of trauma and vulnerability analyzing how personal suffering, familial dysfunction, and spiritual longing shape the novel’s characters and their sense of belonging. Through a close reading of the Pickles and Lamb families, the study argues that Winton presents trauma as a collective inheritance that defines the postwar Australian consciousness rather than as an isolated psychological condition. The novel’s physical and emotional settings—especially the haunted house on Cloud Street—operate as metaphors for buried histories and collective wounds. Fish Lamb’s near-death experience and fragmented awareness embody the psychic rupture of trauma while simultaneously opening the possibility of grace and transcendence. By foregrounding acts of compassion, reconciliation, and emotional openness, Winton positions vulnerability as crucial to healing and human connection. Ultimately, Cloudstreet transforms trauma into a generative space for renewal, affirming Winton’s belief in the redemptive power of love, faith, and community amid suffering.